2010
DOI: 10.1128/jvi.01548-09
|View full text |Cite
|
Sign up to set email alerts
|

The Early Gene hhi1 Reactivates Heliothis zea Nudivirus 1 in Latently Infected Cells

Abstract: Heliothis zea nudivirus 1 (HzNV-1), previously known as Hz-1 virus, is an insect virus able to establish both productive and latent infections in several lepidopteran insect cells. Here, we have cloned and characterized one of the HzNV-1 early genes, hhi1, which maps to the HindIII-I fragment of the viral genome. During the productive viral infection, a 6.2-kb hhi1 transcript was detectable as early as 0.5 h postinfection (hpi). The level of transcript reached a maximum at 2 hpi and gradually decreased after 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…1), for which the highest genome content similarities (six unique genes) have been found (27). HzNV is able to develop particular infection strategies such as having a tropism for gonadal cells (31) and the establishment of latent infections (32). Both of these mechanisms could have been instrumental for the evolution of bracoviruses.…”
Section: Discussionmentioning
confidence: 99%
“…1), for which the highest genome content similarities (six unique genes) have been found (27). HzNV is able to develop particular infection strategies such as having a tropism for gonadal cells (31) and the establishment of latent infections (32). Both of these mechanisms could have been instrumental for the evolution of bracoviruses.…”
Section: Discussionmentioning
confidence: 99%
“…In the HzNV-1 transcripts, the early gene hhi1 (HzNV-1 HindIII fragment 1 gene) contains 270 nucleotides (nts) of 5' untranslated region (UTR) which, together with its upstream 62 bps, compose hhi1 early promoter (Wu et al 2008, Wu et al 2010; the HzNV-1 late gene p34 (ORF79) possesses 16 and 17 nts of 5' UTR, respectively, differing by 1 nt, and both 5' UTRs overlap with the identified 9 bp late promoter motif of the p34 (Guttieri and Burand 1996); as for the HzNV-1 late gene p51 (ORF64), the major late transcriptional initiation site is at −205 bp relative to the translational start codon and seven minor late start sites locate at various positions upstream of this primary site (Guttieri and Burand 2001). The putative www.intechopen.com polyadenylation signals (AATAAA) downstream of the stop codon of the p34 and p51 were found Burand 1996, Guttieri and.…”
Section: Untranslated Regionsmentioning
confidence: 99%
“…Such transactivation is due to the function of ie1 and p35 genes of this heterologous virus (50). We have reported before that hhi1 can serve as a transcriptional activator and is involved in viral reactivation from latently infected cells (50,51). Also, during latent viral infection, only one transcript derived from persistency-associated gene 1 (pag1) was detectable.…”
mentioning
confidence: 99%
“…The HzNV-1 virus has a relatively broad host range and has been reported to productively and latently infect many insect cell lines (4,14,24,31,34,35,40). Previously, we found that more than 100 transcripts are produced during productive HzNV-1 virus infection (6); during this phase of infection, a gene located on the HzNV-1 HindIII-I fragment (hhi1) was found to generate an abundant 6.2-kb transcript within 0.5 h postinfection (hpi) (50,51). In contrast to the expression pattern of many early genes of baculovirus, the expression of hhi1 requires the assistance of HzNV-1 viral infection (51).…”
mentioning
confidence: 99%
See 1 more Smart Citation